2017
DOI: 10.1021/jacs.7b05160
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic 1,3-Difunctionalization via Oxidative C–C Bond Activation

Abstract: Electronegative substituents arrayed in 1,3-relationships along saturated carbon frameworks can exert strong influence over molecular conformation due to dipole minimization effects. Simple and general methods for incorporation of such functional group relationships could thus provide a valuable tool for modulating molecular shape. Here, we describe a general strategy for the 1,3-oxidation of cyclopropanes using aryl iodide(I–III) catalysis, with emphasis on 1,3-difluorination reactions. These reactions make u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(64 citation statements)
references
References 47 publications
0
63
0
1
Order By: Relevance
“…The introductiono fe lectronw ithdrawing groups into the arene counterpart has as imilarly negative effect on the coupling step due to the decrease of the arene nucleophilicity.T hus, attempts to couple 4-nitroiodobenzene and tolueneo r4-iodotoluene and nitrobenzene were unsuccessful. On the other hand, the introductiono fe lectron donating groups into the aryl iodides and arenesi se xpected to decreaset he oxidation potentials of the aryl iodides and increase the nucleophilicity of the arenes, which could improve the reaction efficiency.I ndeed, 4,4'-dimethoxydiphenyliodonium salt (8)i sformedi n4 2% from the electrolysis of 4-methoxyiodobenzene (1c)a nd anisole (7)i na cetic acid containing 2% acetic anhydride and5%s ulfuric acid (Scheme 4). The stability of the electron-rich arenes in the reactionm ediumi s, however, am ajor issue as anisoleu ndergoes sulfonation.…”
Section: Electrochemical Synthesis Of Diaryliodonium Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introductiono fe lectronw ithdrawing groups into the arene counterpart has as imilarly negative effect on the coupling step due to the decrease of the arene nucleophilicity.T hus, attempts to couple 4-nitroiodobenzene and tolueneo r4-iodotoluene and nitrobenzene were unsuccessful. On the other hand, the introductiono fe lectron donating groups into the aryl iodides and arenesi se xpected to decreaset he oxidation potentials of the aryl iodides and increase the nucleophilicity of the arenes, which could improve the reaction efficiency.I ndeed, 4,4'-dimethoxydiphenyliodonium salt (8)i sformedi n4 2% from the electrolysis of 4-methoxyiodobenzene (1c)a nd anisole (7)i na cetic acid containing 2% acetic anhydride and5%s ulfuric acid (Scheme 4). The stability of the electron-rich arenes in the reactionm ediumi s, however, am ajor issue as anisoleu ndergoes sulfonation.…”
Section: Electrochemical Synthesis Of Diaryliodonium Saltsmentioning
confidence: 99%
“…Hypervalent iodine reagents are widely used in modern organic synthesis. [1][2][3][4] These reagents have tremendous synthetic applications,i ncluding difunctionalization of olefins and cyclopropanes, [5][6][7] oxidative couplings, [8][9][10] phenol dearomatizations, [11,12] oxidative formation of heterocycles, [13][14][15][16] aminations, [17,18] halogenations, [19][20][21] arylations, [22][23][24] and rearrangements. [25][26][27][28] In addition, aw ider ange of stereoselective transformationsw as achieved with high degree of stereocontrol using chiral hypervalent iodine reagents and catalytic systems of chiral iodoarenes and terminal oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…11, 14 , 15 Current liabilities of hypervalent iodine reagents include the frequent need for stoichiometric reagent loading and the synthesis of these reagents from wasteful metal-based oxidants, such as KMnO4, NaIO4, and oxone, or organic peracids, such as m-CPBA. [11][12][13]16 No methods are available for the direct synthesis of hypervalent iodine compounds from O2. 17 We were attracted to aerobic oxidation of aryl iodides based on the hypothesis that the resulting hypervalent iodine reagents, in conjunction with ligand exchange at iodine, could provide a new platform for oxidase chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Most of the existing cyclopropane ring-opening approaches have relied on the specific functional group assistance,i ncluding 1) polarizing one of the CÀCb onds through the attachment of an activated donor-acceptor cyclopropane, [3] and 2) the attachment of directing groups that favor oxidative addition by at ransition metal to form metallacyclobutane intermediates (Figure 1a). [5] Some elegant research works have recently demonstrated that they could undergo 1,3-addition of B(C 6 F 5 ) 3 / t Bu 3 P, [6] 1,3-aminofluorination, [7] 1,3difluorination, [8] 1,3-deoxygenation, [9] and elimination [10] reactions.N evertheless,t he development of new systems for efficient opening and functionalization of these compounds under mild and environmentally friendly conditions is still in high demand. [5] Some elegant research works have recently demonstrated that they could undergo 1,3-addition of B(C 6 F 5 ) 3 / t Bu 3 P, [6] 1,3-aminofluorination, [7] 1,3difluorination, [8] 1,3-deoxygenation, [9] and elimination [10] reactions.N evertheless,t he development of new systems for efficient opening and functionalization of these compounds under mild and environmentally friendly conditions is still in high demand.…”
mentioning
confidence: 99%
“…[4] Although non-activated cyclopropanes are the most common threemembered ring systems found in nature,m ethods for their selective ring-opening remain scarce. [5] Some elegant research works have recently demonstrated that they could undergo 1,3-addition of B(C 6 F 5 ) 3 / t Bu 3 P, [6] 1,3-aminofluorination, [7] 1,3difluorination, [8] 1,3-deoxygenation, [9] and elimination [10] reactions.N evertheless,t he development of new systems for efficient opening and functionalization of these compounds under mild and environmentally friendly conditions is still in high demand.…”
mentioning
confidence: 99%